Strategies to Reduce Rework in Software Development on IT Organization Case Study of: PT. XYZ - Kurniawan, Nurul Kholis (Journal of Applied Information, Communication and Technology, 2018)
Today’s world, developing an application that meets exactly the need of organizational business is getting tougher and more challenging, with the additional complexity of business flow and the increasing and diversity of the data that an organization has. In addition, the customers are more demanding than before in term of using an information system or software application and within an instant result which gives an extra pressure for those who work as an application developer. Rework of the software application tends to contain very negative impact to the company because it is impacting the cost for the organization. This paper is trying to resolve the problem that causes a lot of rework occurred in the case study provided. By finding out the root cause of the problem, the literature study is conducted in order to have some recommendations to be applied to the case study given. After having a discussion by conducting interview session with the expert, the result in form of a recommendation is then defined. As the final result, it is decided that the best and most appropriate recommendation to be applied is by implementing System Configuration Management (SCM) and the SMC tools chosen is Team Foundation Server or usually called as TFS.